2009
DOI: 10.1080/01140671.2009.9687586
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of corm and cormel production in gladiolus (Gladiolusspp.)

Abstract: The gladiolus (Gladiolus spp.) industry is based on its flower and also its corm production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 3 publications
1
41
0
Order By: Relevance
“…When translated in terms of yield of corms per unit stock, plantation with quarter corms, showed maximum increase in yield over control (no improved cultural technique), followed by that with half corms. Memon et al (2009a) almost obtained the same results by using half corms. They obtained half corms from whole corms with diameter of 3.6 to 3.8 cm ( Figure 3).…”
Section: Corm Divisions and Sizessupporting
confidence: 57%
See 1 more Smart Citation
“…When translated in terms of yield of corms per unit stock, plantation with quarter corms, showed maximum increase in yield over control (no improved cultural technique), followed by that with half corms. Memon et al (2009a) almost obtained the same results by using half corms. They obtained half corms from whole corms with diameter of 3.6 to 3.8 cm ( Figure 3).…”
Section: Corm Divisions and Sizessupporting
confidence: 57%
“…A number of improved techniques are used to promote corm and cormel production in Gladiolus. The research work was reported on divisions of the corms (Singh and Dohare, 1994;Memon et al, 2009a), removal of flower spikes (El-Gamassy and Sirry, 1967;Wilfret and Raulston, 1974;Mukhopadhyay and Das, 1977; Sprouting on the basis of number of sprouts (Source: http://www.shutterstock.com/pic-3075215/stock-photo-one-gladiolus-flowerbulb-brightly-lit-isolated-on-white.html). al., 1978;Misra, 1994;Singh and Dohare, 1994;Memon et al, 2009a), leaf clippings (Misra, 1994;Memon et al, 2009a), corm sizes (Farid Uddin et al, 2002;Memon et al, 2009b), manual removal of apical buds (Singh and Dohare, 1994) and mechanical removal of sprouts in succession during storage (Sharga and Basario, 1976;Misra, 1994).…”
Section: Propagation Of Corms and Cormels Through Improved Conventionmentioning
confidence: 99%
“…The previous observations showed the clonal growth in Gladiolus cultivars (Rameau & Gouyon, 1991) and its great enhancement after the clipping of leaves and inflorescences (Memon et al, 2009) or the adding of fertiliser (Ali et al, 2014;Saeed et al, 2014;Khattab et al, 2016). Successful clonal growth was also observed in other tuberous taxa such as Dicentra canadensis (Lin et al, 2016) and Crocus sativus (Negb et al, 1989).…”
Section: Discussionmentioning
confidence: 94%
“…Gladiolus (Gladiolus x grandiflorus), which belongs to the Iridaceae family, is cultivated in all world and has a great importance in the international market of flowers (MEMON et al, 2009;MAHASEN et al, 2015). It is a cut flower propagated by corms (SCHWAB et al, 2015a), which is a propagative material in high demand in the foreign market.…”
Section: Introductionmentioning
confidence: 99%